Pharmacokinetic comparison with different assays for simultaneous determination of cis-, trans-cefprozil diastereomers in human plasma - Seung-Hyun Jeong; Ji-Hun Jang; Hea-Young Cho; Yong-Bok Lee (Elsevier, 2021)
The purpose of this study was to compare pharmacokinetic (PK) parameters obtained using two newly developed assays, HPLC-UV and UPLC-ESI-MS/MS. Selection of assay and results obtained therefrom are very important in PK studies and can have a major impact on the PK-based clinical dose and usage settings. For this study, we developed two new methods that are most commonly used in biosample analysis and focused on PK parameters obtained from them. By HPLC-UV equipped with a Luna-C8 column using UV detector, cefprozil diastereomers were separated using water containing 2% (V/V) acetic acid and acetonitrile as a mobile phase. By UPLC-ESI-MS/MS equipped with a HALO-C18column, cefprozil diastereomers were separated using 0.5% (V/V) aqueous formic acid containing 5 mM ammonium-formate buffer and methanol as a mobile phase. Chromatograms showed high resolution, sensitivity, and selectivity without interference by plasma constituents. Both intra- and inter-day precisions (CV, %) were within 8.88% for HPLC-UV and UPLC-ESI-MS/MS. Accuracy of both methods was 95.67%-107.50%. These two analytical methods satisfied the criteria of international guidance and could be successfully applied to PK study. Comparison of PK parameters between two assays confirmed that there is a difference in the predicted minimum plasma concentrations at steady state, which may affect clinical dose and usage settings. Furthermore, we confirmed possible correlation between PK parameters and various biochemical parameters after oral administration of 1000 mg cefprozil to humans.